Forty dead men [large type] - Casey, Donis (Casey, Donis. Alafair Tucker mystery., 2018)
World War I is over. Alafair is overjoyed that her elder son, George Washington Tucker, has finally returned home from the battlefields of France. Yet she is the only one in the family who senses that he has somehow changed. Gee Dub moves back into his old bunkhouse quarters, but he's restless and spends his days roaming. One rainy day while out riding he spies a woman trudging along the country road. She's thoroughly skittish and rejects his help. So Gee Dub cannily rides for home to enlist his mother in offering the exhausted traveler shelter. Once made comfortable at the Tucker farm, Holly Johnson reveals she's forged her way from Maine to Oklahoma in hopes of finding the soldier she married before he shipped to France. At the war's end, Daniel Johnson disappeared without a trace. It's been months. Is he alive? Is she a widow? Holly is following her only lead - that Dan has connected with his parents who live yonder in Okmulgee. Gee Dub, desperate for some kind of mission, resolves to shepherd Holly through her quest although the prickly young woman spurns any aid. Meanwhile, Alafair has discovered that Gee Dub sleeps with two cartridge boxes under his pillow - boxes containing twenty "dead men" each. The boxes are empty, save for one bullet. She recognizes in Gee Dub and Holly that not all war wounds are physical. Then Holly's missing husband turns up, shot dead. Gee Dub is arrested on suspicion of murder, and the entire extended Tucker family rallies to his defense. He says he had no reason to do it, but the solitary bullet under Gee Dub's pillow is gone. Regardless, be he guilty or innocent, his mother will travel any distance and go to any lengths to keep him out of prison.